2009
DOI: 10.1086/605439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Features of HumanPlasmodium knowlesiInfection

Abstract: Knowlesi malaria causes a wide spectrum of disease. Most cases are uncomplicated and respond promptly to treatment, but approximately 1 in 10 patients develop potentially fatal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
362
5
19

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(433 citation statements)
references
References 29 publications
30
362
5
19
Order By: Relevance
“…In Malaysian Borneo, the prevalence of mixed P. knowlesi-P. vivax infections appears to be low, with only one reported PCR-confirmed case in Sarawak (14) and 5/387 (1.3%) in our recent prospective study in Sabah (15). A separate study in Sabah reported 83 P. knowlesi-P. vivax mixed infections (35) but used earlier PCR primers that can include a false-positive P. vivax result for true P. knowlesi monoinfections (32).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Malaysian Borneo, the prevalence of mixed P. knowlesi-P. vivax infections appears to be low, with only one reported PCR-confirmed case in Sarawak (14) and 5/387 (1.3%) in our recent prospective study in Sabah (15). A separate study in Sabah reported 83 P. knowlesi-P. vivax mixed infections (35) but used earlier PCR primers that can include a false-positive P. vivax result for true P. knowlesi monoinfections (32).…”
Section: Discussionmentioning
confidence: 98%
“…In Malaysian Borneo, P. knowlesi is the most common cause of human malaria (10,11) and commonly causes severe disease, with fatal cases also reported (12)(13)(14)(15)(16). Early diagnosis of P. knowlesi infection is important; with its 24-h life cycle, it can rapidly cause high parasitemia and is three times as likely as P. falciparum to cause severe malaria (15).…”
mentioning
confidence: 99%
“…Brevemente, la PCR1 se llevó a cabo en un volumen total de 50 µl de reacción conteniendo 1X de Buffer, 2 mM de MgCl 2 Los productos de PCR fueron sometidos a corrida electroforética en gel de agarosa al 2%, en buffer TAE 1X. El gel fue teñido en bromuro de etidio y visualizado en un transiluminador UV de la marca UVDI Major Science.…”
Section: Extracción Y Amplificación De Adnunclassified
“…La infección con P. ovale se ha reportado principalmente en África oriental con una prevalencia del 56%, también ha sido reportada en Bangladesh, India y países del sudeste Asiático como Vietnam, Filipinas, Indonesia, Papua Nueva Guinea, Camboya, Tailandia y Malasia (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
unclassified
“…The Plasmodium knowlesi parasite replicates and completes its blood stage cycle in 24 hour which leads to high parasite counts in a very short period of time, [4] which may result in massive erythrocyte destruction in patients [5] and complications such as respiratory distress, abnormal liver function including jaundice and renal failure [6]. Hunan infections of Plasmodium Knowlesi malaria has been recorded in some number of countries such as Malaysia, Thailand, China, Singapore, Philippines, Vietnam, Myanmar and Indonesian [4,7].…”
Section: Introductionmentioning
confidence: 99%